Each Student May Learn - Antil, Usha; Singh, Ajit (JOURNAL OF INDIAN EDUCATION, 2013)
Dr. Howard Gardner, Professor of Education at Harvard University developed in 1983 the theory of Multiple Intelligence. He criticised the notion that intelligence is a unitary concept. He held the view that the traditional notion of intelligence does not take into account the entire human potential. He mentioned that each human being is born with 8 intelligences. They spring from different areas of the brain. These separate intelligences have their specific sets of abilities. But all these intelligences are not equally developed in an individual. Dr. Gardener mentioned that each child is talented and has a unique way of thinking and learning. But his/her ways of learning are not addressed in verbally and logically mathematical dominated classrooms. He therefore, pleads that teachers should teach in a variety of ways to match his/ her teaching style to match the learning style of his/her students. Learning style of a child is determinated by highly developed intelligences and less developed intelligences. He therefore, highlights that there are eight pathways to learning. As such, students with different sets of intelligences are sitting in a classroom. The variety of ways of teaching would match different learning styles of students in a classroom. In this way each child in the classroom would get the opportunity to learn.